The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s1470-0328(02)01948-1
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance after hysteroscopic metroplasty in the hypoplastic uterus: a study of 29 cases

Abstract: Objective To evaluate the reproductive performance after hysteroscopic metroplasty performed for hypoplastic uterus. Design Crossover study (15 patients) and descriptive analysis (14 patients).Setting Tertiary care university hospital.Population Twenty-nine women (mean age: 31.4 years; range: 27 -38.5 years) with a hypoplastic malformed uterus and a history of primary infertility and/or recurrent abortion and/or preterm delivery were included in this study. Fourteen women suffered from primary infertility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Despite many recent advances in assisted reproduction techniques even with the selection of good quality embryos, the rate of success is mainly limited because of implantation failures [7,8,16] Endometrial factors at the molecular level have been suggested to explain implantation failure and poor reproductive potential of patients with polycystic ovary syndrome [1,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite many recent advances in assisted reproduction techniques even with the selection of good quality embryos, the rate of success is mainly limited because of implantation failures [7,8,16] Endometrial factors at the molecular level have been suggested to explain implantation failure and poor reproductive potential of patients with polycystic ovary syndrome [1,7].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of this condition in women of the reproductive age is approximately between 5% and 10% [1,4,5]. Polycystic ovary syndrome as a complex disorder is associated with several health complications including obesity, hyperandrogenism, metabolic syndrome, hirsutism, acne, ovarian dysfunction, and infertility [4,6,7]. Although anovulation is an obvious cause of infertility in polycystic ovary syndrome, growing evidence suggests that endometrial receptivity also contributes to infertility of these patients [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the ApoB/ApoA1 ratio reflects the status of pro-and antiatherogenic lipoproteins, and is a marker of MS and CVD [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the defects are treatable [6]. Rates of conception after hysteroscopic metroplasty in septate uterus, or hysteroscopic cutting of intra-uterine adhesion are stated to be high with 87% conception rate postoperatively [7].…”
mentioning
confidence: 99%